Development of LKPD based on ethnomathematics of batik motifs typical of Magelang to increase understanding of the concept of geometric transformation - Venanda Amanatun Septena; Megita Dwi Pamungkas; Fadhilah Rahmawati (Universitas Sarjanawiyata Tamansiswa, 2023)
The existence of a Student Worksheet (LKPD) is able to improve the ability to understand students' concepts. This research aims to develop LKPD based on ethnomathematics of batik motifs typical of Magelang in terms of the ability to understand concepts based on validity, practicality, and effectiveness in geometric transformation materials. The type of research used is research and development (R&D) with a 4D model, namely the defining stage, the design stage, the development stage, and the deployment stage. This study was conducted at SMP Negeri 1 Tegalrejo with a sample of 31 students in class IX B. The results showed that an LKPD based on ethnomathematics of batik motifs typical of Magelang was produced to increase understanding of the concept of geometric transformation that is valid or feasible in terms of the validity value of LKPD by material expert validators and teaching material expert validators, which is 86.31% with a very valid category. Judging from the practicality value of LKPD by the response of students, which is 89.61% with a very practical category. The results of the standard gain increased concept understanding ability were obtained by 5 low classification learners, 10 medium classification students, and 16 high classification students. Increasing understanding of the concept of geometric transformation using LKPD based on ethnomathematics of batik motifs typical of Magelang in terms of the effectiveness value of the pretest and posttest results calculated using the standard gain formula <g> , which is 0.62 with a moderate category, so that LKPD is said to be effective.